ANALISIS PENGELOLAAN MODAL KERJA UNTUK MENILAI RETURN ON INVESTMENT PADA PT GUDANG GARAM, TBK YANG TERDAFTAR DIBURSA EFEK INDONESIA TAHUN 2016-2017 - Fadillah Utami; Mursalin Mursalin; Emma Lilianti (Universitas Nusa Cendana, 2023)
This study aims to determine working capital management as measured by Working Capital Turnover, Cash Turnover, Accounts Receivable Turnover, and Inventory Turnover to assess Return on Investment (ROI) at PT Gudang Garam, Tbk during the 2016–2020 period. This study uses quantitative methods. The results of Working Capital Turnover indicate that the calculation of Working Capital at PT Gudang Garam, Tbk is in